Dynamics and energetics of PCBP1 binding to severely oxidized RNA - Gillet, Natacha; Dumont, Elise (Frontiers in Molecular Biosciences, 2022)
Oxidatively-generated lesions such as 8-oxo-7,8-dihydroguanine (8-oxoG) on RNA strands constitute a hallmark marker of the oxidative stress in the cell. The poly-C binding protein 1 (PCBP1) is able to specifically recognize severely damaged RNA strands containing two 8-oxoG separated by five nucleobases which triggers a signaling pathway leading to the cell apoptosis. We apply an in silico protocol based on microsecond timescale all-atom classical molecular dynamics simulations associated with conformational and energy analysis to unveil the specific recognition mechanism at a molecular level. By comparing the RNA and protein behavior for sequences with six different damage profiles, our results highlight an allosteric mechanism allowing a stronger binding of the oxidized guanine at the 9th position only if another 8-oxoG is present at position 15th, in full agreement with experiments. We assess the role of the lysine K23 and the additional ketone group of the oxidized guanine thanks to computational site-directed mutagenesis.